Overexpression, extraction, purification and characterisation of DppA from Escherichia coli (Journal of Biochemistry, Microbiology and Biotechnology, 2014)
Components such as protein within the periplasmic space serve some vital purposes: such as buffering against the outside environment, processing of essential nutrients for transport into the cytoplasmic space, and cell wall biosynthesis. Dipeptide binding protein a (DppA) is a member of a family of ABC proteins and is involved in the transportation of potentially beneficial dipeptides as nutrient source through the periplasmic space and into cell. DppA was successfully cloned into expression vectors and over expressed in Escherichia coli, extracted, purified, and characterized. DppA was subjected to biophysical characterization using mass spectrometry. Mass spectrometry (ms) analysis and analytical ultra-centrifugation were used to evaluate the recombinant DppA’s molecular weight. The findings presented in this study highlighted the ability to overexpress, extract and purify the recombinant DppA and reflect the differences techniques to asses its purity.